Life cycle contract as an alternative to traditional public procurement - Ешимова, Д.; Нурсеитов, A.; Шерова, Г. (Journal of Economic Research & Business Administration, 2017)
Some common applications of public-private partnerships in foreign countries are transport, infrastructure, health and education. Recently, much attention is paid to a specific type of PPP – life cycle contract (LCC). The adopted in Kazakhstan in October 2015 on public-private partnership law allows the use of LCC. This article describes the features of the life cycle contract, its advantages and disadvantages in order to improve the efficiency of the public sector and summarizes the practical experience of the foreign use of the life cycle contract. As the authors of the research objectives was determined attempt to assess the life cycle contract as an alternative to traditional public procurement. This problem is poorly understood in Kazakhstan and requires further scientific research. Given the vast territory of the country and especially the development of the subjects in the article recommends the use of LCC, especially at the regional level to create a transport infrastructure.